Cognitive and functional resilience despite molecular evidence of Alzheimer's disease pathology. Issue 3 (5th November 2012) - Negash, Selam; Xie, Sharon; Davatzikos, Christos; Clark, Christopher M.; Trojanowski, John Q.; Shaw, Leslie M.; Wolk, David A.; Arnold, Steven E.
Abstract: Background: The correlation between neuropathological lesions and cognition is modest. Some individuals remain cognitively intact despite the presence of significant Alzheimer's disease (AD) pathology, whereas others manifest cognitive symptoms and dementia in the same context. The aim of the present study was to examine cognitive and cerebral reserve factors associated with resilient functioning in the setting of AD pathology. Methods: University of Pennsylvania Alzheimer's Disease Center research participants with biochemical biomarker evidence of AD pathology (cerebrospinal fluid amyloid‐β1‐42 <192 pg/mL) and comparable medial temporal lobe atrophy were categorized by Clinical Dementia Rating Scale‐Sum of Boxes (CDR‐SOB) score as AD dementia (CDR‐SOB >1) or AD resilient (CDR‐SOB ≤0.5). Groups were compared for a variety of demographic, clinical, and neuroimaging variables to identify factors that are associated with resilience to AD pathology. Results: A univariate model identified education and intracranial volume (ICV) as significant covariates. In a multivariate model with backward selection procedure, ICV was retained as a factor most significantly associated with resilience. The interaction term between ICV and education was not significant, suggesting that larger cranial vault size is associated with resilience even in the absence of more education. Conclusions: Premorbid brain volume, as measured through ICV, provided protection against clinical manifestations of dementia despite evidence of significant accumulations of AD pathology. This finding provides support for the brain reserve hypothesis of resilience to AD.